2019
DOI: 10.1101/674135
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Epidemiological consequences of enduring strain-specific immunity requiring repeated episodes of infection

Abstract: GAS are under development, but their effective use will require better understanding of how immunity develops following infection. Evidence from an animal model of skin infection suggests that the generation of enduring strain-specific immunity requires two infections by the same strain within a short time frame. It is not clear if this mechanism of immune development operates in humans, nor how it would contribute to the persistence of GAS in populations and affect vaccine impact. We used a mathematical model… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…• The period diversity of ATs: It is a measure of the number and evenness of ATs in circulation in the population over a period of time. It demonstrates how many antigenic types circulating in the population as well as the evenness among the number of infections by each AT in a given time interval u (Smeesters et al, 2009;Chisholm et al, 2020). We use Simpson's reciprocal index to calculate period diversity, D(t):…”
Section: Multi-strain Transmission Modelmentioning
confidence: 99%
See 4 more Smart Citations
“…• The period diversity of ATs: It is a measure of the number and evenness of ATs in circulation in the population over a period of time. It demonstrates how many antigenic types circulating in the population as well as the evenness among the number of infections by each AT in a given time interval u (Smeesters et al, 2009;Chisholm et al, 2020). We use Simpson's reciprocal index to calculate period diversity, D(t):…”
Section: Multi-strain Transmission Modelmentioning
confidence: 99%
“…Our conceptual framework for understanding the interaction between direct and indirect competition in multi-strain systems (Figure 8) can help us to interpret the observations of certain multi-strain pathogens. For example, it has been suggested that a Group A Streptococcus infection results in an antigen-specific host immune response, however, there is not yet consensus on the duration of immunity after an infection and the strength of within-host competition among strains (Pandey et al, 2016;Hysmith et al, 2017;Chisholm et al, 2020Chisholm et al, , 2021.…”
Section: Inferring Details Of the Host Immune Response To Multi-strai...mentioning
confidence: 99%
See 3 more Smart Citations